Outcome of Hydroxyurea Use in SCD and Evaluation of Patients’ Perception and Experience in Nigeria - Chianumba, Reuben Ikechukwu; Ofakunrin, Akinyemi O. D.; Morrice, Jack; Olanrewaju, Olaniyi; Oniyangi, Oluseyi; Kuliya-Gwarzo, Aisha; Nnebe-Agumadu, Uche; Isa, Hezekiah Alkali; Nnodu, Obiageli Eunice (Frontiers in Genetics, 2022)
Introduction: Hydroxyurea (HU) has been shown to be beneficial in the management of sickle cell disease (SCD) as it improves treatment outcomes. However, despite the benefits of HU, its uptake among SCD patients in Nigeria remains low. Objective: This study aimed to assess the perception and experience of patients with SCD in Nigeria who are using or had used HU, thereby informing and promoting its use. Methodology: A multi-centre, cross-sectional study was conducted among 378 SCD patients aged 1–53 years who have enrolled on Sickle Pan African Research Consortium (SPARCO) registry as HU users. The SPARCO project was funded by the National Institutes of Health (NIH) to establish a sickle cell disease (SCD) registry, strengthen skills and plan research in three African countries. The Nigerian SPARCO registry had 6453 SCD patients at the time of this report with <15% of this population on HU. Data on sociodemographics, perception and experience about HU use were obtained and analysed using descriptive statistics. Findings: Out of the 378 participants, 339 (89.7%) were using HU while 39 (10.3%) had stopped using HU at the time of the study. 281 (74.3%) found HU expensive, while 194 (51.3%) reported none to minimal side effects while using HU. Among patients that stopped HU, cost (59%) and availability (51.3%) were the commonest reasons for discontinuing the drug. Furthermore, 347 (92.5%) had fewer pain crises, 173 (84.8%) had a fewer need for blood transfusion, 145 (86.3%) had improved PCV and 318 (84.6%) had fewer hospital admissions. Finally, the study also showed that 322 (85.2%) respondents would recommend the drug to other patients, whereas 14 respondents (3.7%) would not. Mean corpuscular volume (MCV) and fetal hemoglobin (HbF) levels were not collected in this study and may have improved findings. Conclusion: This study showed that the majority of the SCD patients had good perception and experience with the use of HU while a few had to stop the medication mostly on account of cost and availability. Patients’ based advocacy could be leveraged to improve HU uptake while more efforts are needed to ensure that it is readily available and affordable.